Effects of polysaccharides from Lyophyllum decastes (Fr.) Singer on gut microbiota via in vitro-simulated digestion and fermentation - Zhang, Fangfang; Xiao, Ying; Pan, Liang; Yu, Ling; Liu, Yanfang; Li, Deshun; Liu, Xiaojie (Frontiers in Microbiology, 2023)
Introduction Lyophyllum decastes (Fr.) Singer polysaccharides (LDSPs) have been verified to possess strong biological properties. However, the effects of LDSPs on intestinal microbes and their metabolites have rarely been addressed. Methods The in vitro-simulated saliva-gastrointestinal digestion and human fecal fermentation were used to evaluate the effects of LDSPs on non-digestibility and intestinal microflora regulation in the present study. Results The results showed a slight increase in the content of the reducing end of the polysaccharide chain and no obvious change in the molecular weight during in vitro digestion. After 24 h in vitro fermentation, LDSPs were degraded and utilized by human gut microbiota, and LDSPs could be transformed into short-chain fatty acids leading to significant (p < 0.05) decrease in the pH of the fermentation solution. The digestion did not remarkably affect the overall structure of LDSPs and 16S rRNA analysis revealed distinct shifts in the gut microbial composition and community diversity of the LDSPs-treated cultures, compared with the control group. Notably, the LDSPs group directed a targeted promotion of the abundance of butyrogenic bacteria, including Blautia, Roseburia, and Bacteroides, and an increase in the n-butyrate level. Discussion These findings suggest that LDSPs might be a potential prebiotic to provide a health benefit.